Gray matter volumes may predict the clinical response to paliperidone palmitate long-acting in acute psychosis: A pilot longitudinal neuroimaging study. (30th March 2017) - Altamura, A. Carlo; Delvecchio, Giuseppe; Paletta, Silvia; Di Pace, Chiara; Reggiori, Alessandra; Fiorentini, Alessio; Mirabile, M. Donatella; Paoli, Riccardo A.; Cinnante, Claudia; Triulzi, Fabio; Mauri, Massimo C.; Brambilla, Paolo
Abstract: In schizophrenia, paliperidone palmitate (PP) long acting injectable (LAI) has been reported to sustain plasma concentrations and improve clinical symptoms. Moreover, it has also been demonstrated the important role of total gray matter (GM) volumes in predicting the clinical outcome. However, no studies investigating the association between PP-LAI treatment and brain morphometry has been published so far. Therefore, the main aim of our 24 weeks prospective observational exploratory study was to investigate the relation between brain anatomy and clinical outcome in seven patients with acute psychosis treated with PP-LAI. At baseline and every month (from T0 to T6) patients were clinically evaluated with the Brief Psychiatric Rating Scale (BPRS). 3 T Magnetic Resonance Imaging at baseline was acquired and total GM and intracranial volumes were extracted to explore their predictive values on BPRS scores. After 24 weeks of treatment with PP-LAI, patients showed statistically significant improvements in BPRS scores. Moreover, subjects with higher total GM volumes had a significantly higher BPRS improvement at 24 weeks compared to patients with lower total GM volumes. Our findings confirm the effectiveness of PP-LAI in treating acute psychosis and suggest that greater GM volumes predict drug response, potentially supporting a favorable prognosis. Highlights: 24 weeks prospective observational study in patients treated with PP-LAI. Beneficial therapeutic effect of PP-LAI after 24 weeks of treatment. Greater brain volumes predict drug response supporting a favorable prognosis.